2020
DOI: 10.1093/jat/bkaa157
|View full text |Cite
|
Sign up to set email alerts
|

Heroin-Related Compounds and Metabolic Ratios in Postmortem Samples Using LC–MS-MS

Abstract: Analysis of postmortem samples with the presence of morphine can sometimes be challenging to interpret. Tolerance complicates interpretation of intoxications and causes of death due to overlap in therapeutic and fatal concentrations. Determination of metabolites and metabolic ratios can potentially differentiate between abstinence, continuous administration, and perhaps time of administration. The purpose of this study was to (a) develop and validate a method for quantitation of morphine-3β-D-glucuronide, morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…This has been described for e.g. buprenorphine (26), and heroin (27,28). A negative opioid result in urine or hair can suggest short-term abstinence or long-term abstinence which could possibly explain the events leading to death.…”
Section: Discussionmentioning
confidence: 93%
“…This has been described for e.g. buprenorphine (26), and heroin (27,28). A negative opioid result in urine or hair can suggest short-term abstinence or long-term abstinence which could possibly explain the events leading to death.…”
Section: Discussionmentioning
confidence: 93%
“…The in vitro and in vivo study of the metabolic profile of NPS is a useful tool for providing data. This may be useful in terms of diagnosis, assessment of the severity of poisoning and treatment for the purposes of clinical toxicology, or the toxicological distinction of “rapid deaths” and “delayed deaths” [ 24 , 25 ], predicting possible post mortem redistribution processes and their impact on the final result of determinations for the purposes of medical and forensic opinion.…”
Section: Resultsmentioning
confidence: 99%
“…The level of codeine was low in all age groups (median, 20–35 ng/mL), which could be explained by the fact that 6-AC is metabolized to codeine and codeine-6-glucuronide (C6G) faster than to other compounds. A recently published study demonstrated that C6G was not detected in blood samples obtained from authentic postmortem cases following heroin intake, while codeine was [ 42 ]. In another study, codeine was always higher than C6G in autopsy blood samples from heroin- and codeine-related fatalities [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of blood-free morphine/total morphine ratios in the blood to identify the cause and mode of death has been reported [ 18 , 42 ]. However, this approach always involves certain issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation